2014
DOI: 10.1681/asn.2013040355
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Iron-Regulatory Hepcidin by Vitamin D

Abstract: The antibacterial protein hepcidin regulates the absorption, tissue distribution, and extracellular concentration of iron by suppressing ferroportin-mediated export of cellular iron. In CKD, elevated hepcidin and vitamin D deficiency are associated with anemia. Therefore, we explored a possible role for vitamin D in iron homeostasis. Treatment of cultured hepatocytes or monocytes with prohormone 25-hydroxyvitamin D or active 1,25-dihydroxyvitamin D decreased expression of hepcidin mRNA by 0.5-fold, contrasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
264
7
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(306 citation statements)
references
References 50 publications
19
264
7
4
Order By: Relevance
“…and SFC levels could be attributed to a modulatory effect for VD on hepcidin/Fpn pathway inducing more iron release, thus increasing SFC, to be available for more synthesis of hemoglobin, so increasing Hb conc. These findings and assumption supported that previously reported by Bacchetta et al (10) who documented that VD is a potent regulator of the hepcidin-Fpn axis in humans and Azizi-Soleiman et al (32) who found VDD is associated with higher hepcidin level in the body. Smith & Tangpricha (33) attributed the regulatory effect of VD on hepcidin/Fpn axis to a direct suppression of hepcidin mRNA transcription.…”
Section: Discussion:-supporting
confidence: 91%
See 2 more Smart Citations
“…and SFC levels could be attributed to a modulatory effect for VD on hepcidin/Fpn pathway inducing more iron release, thus increasing SFC, to be available for more synthesis of hemoglobin, so increasing Hb conc. These findings and assumption supported that previously reported by Bacchetta et al (10) who documented that VD is a potent regulator of the hepcidin-Fpn axis in humans and Azizi-Soleiman et al (32) who found VDD is associated with higher hepcidin level in the body. Smith & Tangpricha (33) attributed the regulatory effect of VD on hepcidin/Fpn axis to a direct suppression of hepcidin mRNA transcription.…”
Section: Discussion:-supporting
confidence: 91%
“…Interestingly, the current study detected a negative association between levels of 25OH-VD and hepcidin. On basis of hepcidin regulatory action on iron homeostasis through its effects on ferroportin (Fpn)-mediated export of cellular iron through binding to Fpn and inducing its internalization (10) , thus the reported positive association between 25OH-VD levels and both Hb conc. and SFC levels could be attributed to a modulatory effect for VD on hepcidin/Fpn pathway inducing more iron release, thus increasing SFC, to be available for more synthesis of hemoglobin, so increasing Hb conc.…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to recognise that intracrine activation of vitamin D promotes antibacterial responses beyond simple induction of cathelicidin and other antibacterial proteins such as b-defensins (Liu et al 2009). These include the induction of autophagy (Shin et al 2011) and possible effects on intracellular iron concentrations via the iron export modulator hepcidin (Bacchetta et al 2014). Crucially, these mechanisms are focused on an intracellular function for vitamin D, and enhanced antibacterial responses to vitamin D are optimal for intracellular pathogens such as M. tuberculosis.…”
Section: Decidual Macrophagesmentioning
confidence: 99%
“…Initially, this was attributed to the anti-inflammatory and pro-erythropoietic effects of vitamin D (46). Data now suggest that vitamin D may actually modulate iron homeostasis via hepcidin, with a study showing that 1,25-dihydroxycholecalciferol directly inhibits hepcidin expression by binding to a vitamin D response element in the gene coding for hepcidin (47).…”
Section: Anaemia Of Ckdmentioning
confidence: 99%